The 330 risk loci known for systemic lupus erythematosus (SLE): a review - Laurynenka, Viktoryia; Harley, John B. (Frontiers in Lupus, 2024)
An in-depth literature review of up to 2023 reveals 330 risk loci found by genetic association at p ≤ 5 × 10−8, with systemic lupus erythematosus (SLE) in at least one study of 160 pertinent publications. There are 225 loci found in East Asian (EAS), 106 in European (EU), 11 in African-American (AA), 18 Mixed American (MA), and 1 in Egyptian ancestries. Unexpectedly, most of these associations are found to date at p ≤ 5 × 10−8 in a single ancestry. However, the EAS and EU share 40 risk loci that are independently established. The great majority of the identified loci [250 (75.8%) of 330] do not contain a variant that changes an amino acid sequence. Meanwhile, most overlap with known regulatory elements in the genome [266 (80.6%) of 330], suggesting a major role for gene regulation in the genetic mechanisms of SLE. To evaluate the pathways altered by SLE-associated variants, we generated gene sets potentially regulated by SLE loci that consist of the nearest genes, published attributions, and genes predicted by computational tools. The most useful insights, at present, suggest that SLE genetic mechanisms involve (1) the regulation of both adaptive and innate immune responses including immune cell activation and differentiation; (2) the regulation of production and response to cytokines, including type I interferon; (3) apoptosis; (4) the sensing and removal of immune complexes and apoptotic particles; and (5) immune response to infections, including Epstein–Barr Virus, and symbiont microorganisms. These mechanisms affected by SLE genes involve multiple cell types, including B cells/plasma cells, T cells, dendritic cells, monocytes/macrophages, natural killer cells, neutrophils, and endothelial cells. The genetics of SLE from GWAS data reveal an incredibly complex profusion of interrelated molecular processes and interacting cells participating in SLE pathogenesis, mostly unified in the molecular regulation of inflammatory responses. These genetic associations in lupus and affected molecular pathways not only give us an understanding of the disease pathogenesis but may also help in drug discoveries for SLE treatment.